Global Trends of Forest Loss Due to Fire From 2001 to 2019 - Tyukavina, Alexandra; Potapov, Peter; Hansen, Matthew C.; Pickens, Amy H.; Stehman, Stephen V.; Turubanova, Svetlana; Parker, Diana; Zalles, Viviana; Lima, André; Kommareddy, Indrani; Song, Xiao-Peng; Wang, Lei; et al. (Frontiers in Remote Sensing, 2022)
Forest fires contribute to global greenhouse gas emissions and can negatively affect public health, economic activity, and provision of ecosystem services (Aragão et al., 2018; Cascio, 2018; Liu et al., 2019). In boreal forests, fires are a part of the ecosystem dynamics (Kasischke and Stocks, 2000), while in the humid tropics, fires are largely human-induced and lead to forest degradation (Cochrane, 2003). Studies have shown changing fire dynamics across the globe due to both climate and land use change (Moritz et al., 2014; Jolly et al., 2015; Andela et al., 2017). However, global trends in fire-related forest loss remain uncertain due to the lack of a globally consistent methodology applied to high spatial resolution data. Here, we create the first global 30 m resolution satellite-based map of annual forest loss due to fire. When producing this map, we match the mapped area of forest loss due to fire to the reference area obtained using a sample-based unbiased estimator, thus enabling map-based area reporting and trend analysis. We find an increasing global trend in forest loss due to fire from 2001 to 2019, driven by near-uniform increases across the tropics, subtropical and temperate Australia, and boreal Eurasia. Results quantify the increasing threat of fires to remaining forests globally and may improve modeling of future forest fire loss rates under various climate change and development scenarios.